Pengaruh Ekstrak Daun Nanas Terhadap Pertumbuhann Candida albicans Dan Malassezia furfur Dalam Bentuk Sediaan Shampo Herbal - Abadi , Hafizhatul; Khairani , Tetty Noverita; Fitri, Khairani; Diana, Vivi Eulis; Leny, Leny; Hasibuan, Amalia Juliani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Dandruff is a common scalp problem often caused by the overgrowth of fungi such as Candida albicans and Malassezia furfur. Pineapple leaves (Ananas comosus (L.) Merr.) are known to contain active antifungal compounds, such as alkaloids, flavonoids, saponins, and tannins, making them a potential active ingredient for anti-dandruff preparations. Objective: This study aimed to formulate an herbal anti-dandruff shampoo using pineapple leaf ethanol extract and to evaluate its effectiveness in inhibiting the growth of Candida albicans and Malassezia furfur. Methods: This experimental research used the disc diffusion method with PDA and SDA media to test antifungal inhibition. The shampoo preparations were formulated with varying extract concentrations (10%, 20%, 30%). The evaluation of the preparations included organoleptic tests, homogeneity, pH, foam height, viscosity, stability (cycling test), skin irritation, and hedonic tests. Results: The resulting shampoo preparation had a blackish-brown color, liquid form, and a menthol odor. Evaluation results showed the preparation was homogeneous, with pH values (5.0-5.8), foam height, and viscosity meeting the requirements. The preparation was also stable during the cycling test and did not cause irritation. The antifungal activity test showed that increasing the extract concentration increased the inhibitory power. The formula with a 30% concentration (F3) provided the greatest inhibition against Candida albicans (average 15.76 mm) and Malassezia furfur (average 15.9 mm), which is categorized as strong. Conclusion: Pineapple leaf ethanol extract was successfully formulated into an effective herbal anti-dandruff shampoo preparation, with the 30% concentration being the most optimal. It is recommended that further research investigate the antifungal activity of this extract against other types of fungi and in different dosage forms.